Brain Drain in North Macedonia: Key Factors and Effective Measures for Human Capital Retention among Employees - Cvetanoska, Marijana; Trpeski, Predrag; Ristovska, Andrijana (My University, 2024)
This paper aims to examine the push factors influencing the intention of employees in North Macedonia to emigrate and identify potential measures to reduce the "brain drain" or “human capital flight” phenomenon. The subject of the study focuses on the attitudes of employees regarding their intention to leave the country, considering variables such as salary growth, promotion opportunities, trust in state institutions, the availability of alternative employment within the country, and employment practices in the country. The research employs a survey methodology, involving 120 respondents from various demographic backgrounds to capture diverse perspectives on the push factors driving emigration. A methodical statistical procedure was applied using simple linear regression to determine the impact of each economic factor on employees' intentions to leave. Additionally, multiple linear regression was utilized to see how various push factors together influence the employees' intention to leave the country. The results reveal that 62% of respondents are inclined to leave the country, particularly younger employees aged 31-40 with higher education levels. The primary factor influencing this intention is the lack of alternative employment opportunities in North Macedonia. These findings underscore the need for targeted policies and measures to retain human capital and prevent further economic and demographic decline.
Keywords: Brain drain; Human capital; Migration; North Macedonia